The Influence of Country of Origin, Celebrity Endorser, and Electronic Word of Mouth on Purchase Decisions for Innisfree Korean Skincare Products - Amanah, Naning Dwi; Randikaparsa, Irawan; Astuti, Herni Justiana; Bagis, Fatmah (International Journal of Business and Applied Economics, 2025)
This research investigates the impact of Country of Origin, Celebrity Endorser, and Electronic Word of Mouth (E-WOM) on the purchasing decisions of Innisfree skincare products among university students. Utilizing a quantitative approach with purposive sampling, the study involved 293 respondents. Data analysis was conducted using the Structural Equation Modeling - Partial Least Squares (SEM-PLS) technique to evaluate the relationships among variables. The results reveal that Country of Origin, Celebrity Endorser, and E-WOM significantly and positively affect purchasing decisions. The study's implications provide insights for consumers to understand how factors such as Country of Origin, Celebrity Endorser, and E-WOM can shape their purchasing decisions.